The Humble Reason. On Education in Kant and Fichte - Scaglia, Lara (ETHICS IN PROGRESS, 2021)
In this paper I will focus on education as the core function of reason in Kant and Fichte. The notion of reason carries an intrinsic tendency to universality, which is difficult to be reconciled with its local (cultural, historical, anthropological) background and actualisation. I believe that the stress on the importance of learning, which can be seen in the works of both Kant and Fichte, might provide useful clues to approaching the relation between universality and particularity. I will start by focusing on Kant’s narration on the genealogy of human reason in the Conjectural Beginning of Human History, and then move on to the critical writings and selected lectures in order to focus on the role of human dignity and ethical education for the moral appraisal and the practice of virtue. Later, I will consider Fichte’s lectures on the Vocation of the Scholar, the Vocation of Man and The Characteristics of the Present Age, which are crucial to understanding the social, ethical and political role of the scholar. For Fichte, education is the best instrument to eradicate selfishness, regarded as a historical phenomenon which can lead a nation to ruin. I will then provide some conclusions concerning the two accounts and their implications.